2019
DOI: 10.1200/jco.2019.37.15_suppl.9500
|View full text |Cite
|
Sign up to set email alerts
|

Phase 3 international trial of adjuvant whole brain radiotherapy (WBRT) or observation (Obs) following local treatment of 1-3 melanoma brain metastases (MBMs).

Abstract: 9500 Background: The role of adjuvant WBRT in MBMs is controversial. This trial compares WBRT with Obs after local treatment of 1-3 MBMs. Methods: The primary endpoint is distant intracranial failure (DIF) within 12 months of randomization. The a priori neurocognitive function (NCF) endpoint is Hopkins Verbal Learning Test-Revised (HVLT-R) delayed recall at 4 months. Secondary endpoints include local failure (LF), overall survival (OS) and global quality of life (QoL). Analyses were conducted on intention-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…An Australian‐led international (ANZMTG‐01.07 WBRTMel) trial specifically investigated the role of adjuvant WBRT in this group of patients . Findings from this single‐histology BM trial have recently been reported to show no improvement in intracranial control with adjuvant WBRT – 12‐month cumulative incidence of intracranial failure was 42% in patients who underwent adjuvant WBRT vs. 51% in patients who did not ( P = 0.16) …”
Section: Discussionmentioning
confidence: 99%
“…An Australian‐led international (ANZMTG‐01.07 WBRTMel) trial specifically investigated the role of adjuvant WBRT in this group of patients . Findings from this single‐histology BM trial have recently been reported to show no improvement in intracranial control with adjuvant WBRT – 12‐month cumulative incidence of intracranial failure was 42% in patients who underwent adjuvant WBRT vs. 51% in patients who did not ( P = 0.16) …”
Section: Discussionmentioning
confidence: 99%
“…Treatment with the above-mentioned drugs is reimbursed in Poland under the B.59 drug reimbursment program. Systemic treatment should be performed in centers that provide full range of therapeutic options [64]. The qualification of patients with metastatic melanoma for prospective clinical trials should still be considered (Fig.…”
Section: Treatment Of Metastatic Patientsmentioning
confidence: 99%